Design 3D Character "Sen" for "Red Wind" Game of PY Studio - Le, Thi Thanh Binh (Vietnam-Korea University of Information and Communication Technology, 2025)
Graduation thesis of Information Technology - Multimedia Communication; 2020 - 2025